نظرية روح المعنى في تفسير ألفاظ متشابه الصفات - دوادي, آمنه; رقيق, عبد الكريم (جامعة الوادي - University of Eloued, 2022)
ملخص: يُبيِّن المقال كيفية توظيف بعض العلماء لنظرية روح المعنى في إثبات حقائق ألفاظ متشابه الصفات؛ فحسب النظرية التي تقدم تفسيرا مغايرا للشائع من الوضع اللغوي: الألفاظ ليست موضوعة لمعان محسوسة فتكون حقيقة فيها ومستعملة في غيرها مجازا، إنما لمعان معقولة قد تكون المعاني المجازية نفسها أو المعنى الجامع لكل المعاني التي استعمل اللفظ للدلالة عليها سواء المحسوسة أو المعقولة، وعليه لا يلزم إثباتَ حقائقها تشبيهُه تعالى، وقد اعتمدها علماء في تفسيرهم لمتشابه الصفات كأبي حامد الغزالي في بعض كتبه والطباطبائي في تفسيره الميزان، ويمكن أيضا ملاحظتها لا على وجه القصد لها، في بعض مؤلفات ابن تيمية، وكذا عالم سبيط النيلي صاحب المنهج القصدي في اللغة. Abstract :The paper shows how som scholars employ The theory of the essence in verifying the trueness of word with unspicific attributes, according to the theory that offers a different interpretation of the common linguistic form, words are not put for denotative meanings so they are real in it and figurative in others, but for rational meanings, the figurative meanings may be the same, or the collective meaningsof all the meanings thatthe word is used to denote, whether denotative or understandable. Therefore it is not essential to pro vits facts of its being similar to Allah almighty. Scholars have approved it in their interpretation of unspicific attributes, such as Abu hamid Al-Ghazali in som of his books, and Al-tabatibai in his interpretation, it can also be perceived, not as intention, in some of Ibn- Taymias books, as well as Alim Sabeit Al-Nili: the author of the intentional approach.
The theory of the essence of meaning in the interpretation of words with unspecific attributes
مقال
Keywords: روح ; المعنى ; تفسير ; متشابه ; الصفات: essence; meaning; interpretation; unspecific; attributes.